Ferroelectric and Dielectric Aging Effects of Fe3+/Nb 5+ hybrid-doped barium titanate ceramics - S. Prasertpalichatr (2018)
It is well known that acceptor and donor doping results in opposite ferroelectric aging effects; however, the aging effects in hybrid-doped (acceptor+donor) has remained unclear. Thus, the aging effect of dielectric and ferroelectric properties in Fe3+/Nb5+ hybrid-doped BaTiO3 ceramics was investigated in this research. The concentration of acceptor dopant (Fe3+) was fixed at 1 mol% while that of donor dopant (Nb5+) was varied from 0.5-2.0 mol%. XRD technique was used to study the phase morphology. Before measuring dielectric and ferroelectric aging effect, all samples were deaged at 250 °C for 1 hour. The results showed that the dielectric properties of all deaged samples have decreased exponentially with time. The deaged samples with 0.5 and 1.0 mol% of Nb 5+ obviously showed double hysteresis loop while that with higher concentration of Nb5+(1.5-2.0 mol%) showed the rectangular (normal) hysteresis loop. The explanations based on the effect of defect dipole were discussed. © 2008 Trans Tech Publications, Switzerland.